2021
DOI: 10.2196/24742
|View full text |Cite
|
Sign up to set email alerts
|

Capturing COVID-19–Like Symptoms at Scale Using Banner Ads on an Online News Platform: Pilot Survey Study

Abstract: Background Identifying new COVID-19 cases is challenging. Not every suspected case undergoes testing, because testing kits and other equipment are limited in many parts of the world. Yet populations increasingly use the internet to manage both home and work life during the pandemic, giving researchers mediated connections to millions of people sheltering in place. Objective The goal of this study was to assess the feasibility of using an online news pla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Some studies suggested that consistent staffing on all days helped to optimize proficiency and helped in cooperation [36], while some studies addressed it through interdisciplinary collaboration and active reinforcement programs implemented [37]. In-formation technology should be fully used in nucleic acid testing, and it was feasible to recruit volunteers and materials through the online news platform [38].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that consistent staffing on all days helped to optimize proficiency and helped in cooperation [36], while some studies addressed it through interdisciplinary collaboration and active reinforcement programs implemented [37]. In-formation technology should be fully used in nucleic acid testing, and it was feasible to recruit volunteers and materials through the online news platform [38].…”
Section: Discussionmentioning
confidence: 99%
“…We used recruitment methods developed during a pilot study by our team and previously published elsewhere [ 28 ]. Briefly, we partnered with Microsoft News to recruit participants to complete a 1-time online survey between February 25 and March 22, 2021.…”
Section: Methodsmentioning
confidence: 99%